Trichoderma spp. in Growth Promotion of Jacaranda Mimosifolia D. Don - Ferreira, Natália Cássia de Faria; Rocha, Ednaldo Cândido; Rodrigues, Fabrício; Santos, Solange Xavier dos; Oliveira, Thiago Alves Santos de; Duarte, Elizabeth Amélia Alves; Carvalho, Daniel Diego Costa (Journal of Agricultural Studies, 2021)
The low volume of information related to the interaction of Trichoderma fungi with seeds and seedlings represents a limitation to forest production, and it is important to carry out studies focusing on its effect on plant germinability and formation. The aim was to evaluate commercial products based on Trichoderma spp. in promoting growth of Jacaranda mimosifolia. For initial seedling growth assay, seeds were treated with Trichoderma spp. suspension and placed on germinating paper sheets. At 28 days after sowing (DAS) the following evaluations were: percentage germination (PG), root length (RL), shoot length (SL), total length (TL), fresh root mass (FRM), fresh shoot mass (FSM), fresh total mass (FTM), root dry mass (RDM), shoot dry mass (SDM) and total dry mass (BIO). To evaluate the development of Jacaranda mimosifolia plants, the experiment was conducted in a greenhouse, wherein the soil of each pot (10 L) was treated with five strains of the Trichoderma spp. (Trichoderma asperellum URM 5911; T. harzianum ESALQ 1306; T. harzianum IBLF 006 WP; T. harzianum SIMBI T5 and T. harzianum T-22 WG. Then, Jacaranda mimosifolia seeds were sown and the evaluations performed at 120 DAS. The variables were: PG at 120 DAS, shoot height (SH), stem diameter (SD), and Dickson quality index (DQI). The strains SIMBI T5, ESALQ 1306 and T-22 WG stood out in relation to RL; while ESALQ 1306 and SIMBI T5 stood out performed the RL and TL. In greenhouse, SIMBI T5 and ESALQ1306 presented higher values of ALT, CR, DC, MFT. Meanwhile, only the SIMBI T5 strain stood out for MSPA, MSR, BIO and DQI.